2020
DOI: 10.1177/0276236620938310
|View full text |Cite
|
Sign up to set email alerts
|

“Imagine All the People”: Imagined Interactions in Virtual Reality When Public Speaking

Abstract: This study explores the relationship between public speaking anxiety (PSA) and Imaginary Interactions (IIs). Participants ( N = 17) were recruited from the multi-section departmental introductory public speaking course. Virtual reality (VR) as a potential form of II treatment for PSA blurs the reality between imagined and actual interactions. This study utilized a sequential explanatory approach to examine inferential and descriptive findings. The inferential investigation employed a four-stage design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Accordingly, "being there" leads to the participants' increase in "intrinsic motivation and engagement" (Dalgarno and Lee, 2010). Ruscella (2019) and LeFebvre et al (2020) suggest that an immersive setting reduces fear and creates a norisk situation that is ideal for learners to practice their speeches.…”
Section: A Complementary Solution: Empirical Evidence On the E Ects O...mentioning
confidence: 99%
“…Accordingly, "being there" leads to the participants' increase in "intrinsic motivation and engagement" (Dalgarno and Lee, 2010). Ruscella (2019) and LeFebvre et al (2020) suggest that an immersive setting reduces fear and creates a norisk situation that is ideal for learners to practice their speeches.…”
Section: A Complementary Solution: Empirical Evidence On the E Ects O...mentioning
confidence: 99%
“…Arvidsson (2006) expounds on the capability of imagination in digital dating, "It is suggested that such 'fantasy work'the work of imagining situations, people, and relationsis activated to an unprecedented extent in the online economy…Dating sites are where the powers of fantasy are stimulated " (p. 672, 678). Imagined interactions (IIs) have similarly been used to describe this type of fantasy/imagination work involved in interpersonal relationships (Honeycutt, 2003(Honeycutt, , 2010(Honeycutt, , 2020LeFebvre et al, 2021;Vickery, 2019) and have a clear use in CMC and digital dating. The present study seeks to apply the interpersonal construct of IIs to CMC, specifically in the realm of online dating, to explore the nature of imagination work while using dating apps and sites.…”
Section: Introductionmentioning
confidence: 99%
“…The training of public speaking physical delivery receives virtually no attention or practice time in the higher education classroom for students [28], even though most colleges and universities include communication skills in their learning outcomes and assessment framework [29]. For example, typical statements usually explicate that "students will demonstrate the ability to construct intelligible messages using sound evidence and reasoning that are appropriate for different rhetorical situations (audience and purposes) and deliver those messages effectively in written, oral, and visual form [30]."…”
Section: Public Speaking Instructionmentioning
confidence: 99%